2015
DOI: 10.1097/md.0000000000001769
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Body Mass Index on the Surgical Outcomes of Patients With Gastric Cancer

Abstract: This study aimed to investigate the impact of body mass index (BMI) on the short-term and long-term results of a large cohort of gastric cancer (GC) patients undergoing gastrectomy.Recently, the “obesity paradox” has been proposed, referring to the paradoxically “better” outcomes of overweight and obese patients compared with nonoverweight patients. The associations between BMI and surgical outcomes among patients with GC remain controversial.A single-institution cohort of 1249 GC patients undergoing gastrecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 37 publications
8
107
3
1
Order By: Relevance
“…Interestingly, Chen et al 63. have concluded that high‐BMI patients exhibit paradoxically ‘superior’ survival outcomes compared with normal‐BMI patients despite the higher risk of mild postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Chen et al 63. have concluded that high‐BMI patients exhibit paradoxically ‘superior’ survival outcomes compared with normal‐BMI patients despite the higher risk of mild postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
“…The BMI was calculated as previously reported (< 18.5 kg/m 2 , ≥ 18.5 to < 25.0 kg/m 2 , ≥ 25.0 kg/m 2 ) and the preoperative body weight loss was categorized as ''<5% of body weight'' or ''≥5% of body weight'' 15, 22.…”
Section: Methodsmentioning
confidence: 99%
“…Study of Lien et al revealed that serum albumin levels were independent factors correlated with prognosis in GC 14. A recent study, including 1249 cases, shown that a low BMI was associated with poorer prognosis in stage III-IV GC patients 15. Furthermore, our previous study reported that preoperative weight loss independently predicted overall survival (OS) in GC 16.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, studies have proved that several nutrition-based indices, such as the prognostic nutritional index (PNI), body mass index (BMI), serum albumin, and preoperative body weight loss, have important prognostic value across varied malignancies, including GC 912. A study of 1,249 cases from Chen et al found that a low BMI might be associated with poorer survival among patients with stage III–IV GC 13. Hinata et al reported that impaired performance status was associated with an unfavorable prognosis in patients with urothelial carcinoma of the bladder who underwent radical cystectomy 14.…”
Section: Introductionmentioning
confidence: 99%